CORRECTION OF PHYSIOLOGICAL STATUS AND REPRODUCTIVE FUNCTION OF SOWS TO THE EFFECT OF DIETARY SUPPLEMENTS - Спіцина, Т. Л.; Ракитянський, В. М.; Сухін, В. М. (Scientific Progress & Innovations, 2014)
The article studied the possibility of using dietary supplements for correcting metabolism and stimulation of reproductive function of sows. The additive activates protein synthesis function of the liver and improves hepatocytes, decreasing the period between weaning and estrus, increased levels of fertilization after the first insemination by 10%. This effect used additives improves blood circulation in the pelvic organs, increases the functional activity of the ovaries by stimulating folliculogenesis and ovulation.